SEROLOGICAL AND MOLECULAR DIAGNOSIS OF TOXOPLASMA GONDII AMONG EWES AND HORSES IN DUHOK PROVINCE-IRAQ - & Al-Saeed, Mikaeel (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
This study was aimed to demonstrate the seroprevalence and molecular detection of Toxoplasma gondii among ewes and horses as well as to determine the risk factors for infection in Duhok province. Sera and blood samples from 700 ewes and 62 horses were collected. Sera were examined by indirect ELISA for detection of anti-T. gondii IgM antibodies and in molecular study, DNA was extracted, then by PCR, B1 gene was amplified and the product visualized and sent off for sequencing. Serologically, the prevalence of toxoplasmosis was 17.7 (11/62) and 28.9 (202/700) in horses and ewes by ELISA respectively. Present of cats on the farm was significantly associated with T. gondii infected ewes in the farm. While, Age, number of abortion and history of abortion has no role in infection in ewes. On the other hand, age and sex have no role in prevalence of toxoplasmosis among the horses. Only 2 samples among 11 seropositive samples by ELISA were give positive results by PCR in rate 18.2% in horse, while in ewes 13 samples from 60 randomly selected seropositive by ELISA were found to be positive by PCR in rate 21.7%. Results of this study indicate that prevalence of T. gondii among ewes and horses was high and cats have a role in prevalence of infection among the ewes.